Suﬁ sm as the direction of Islam and its raspostraneniye in Kazakhstan (Journal of Philosophy Culture and Political Science, 2019)
This article reviews the history of the spread of one of the most important areas in Kazakhstan, Islam – Suﬁ sm. And also about the founder of Suﬁ  poetry, which became the spiritual leader of all Muslims of the East, religious leader, nicknamed «the Sultan of His Holiness.» Unfading through the centuries the precious heritage of our ancestors – «Diwani Hikmet» («Book of Wisdom») – written in Kipchak dialect of ancient Turkic language. Suﬁ  preachers and students of Yasaui A. (1093-1166) – spread his views around the world. Khoja Ahmed identiﬁ ed the direction of spiritual development of the Turkic peoples in the new Islamic civilization. Thanks to A. Yasaui the Suﬁ sm played a crucial role as a philosophical system in the spiritual worldview of the Turkic peoples.